Acoustic Quality Analysis Inside the Black Box Theater Room - Kiki Rezki Lestari; Andika A. Triputranto; Hari Hadi (Global Writing Academica Researching and Publishing, 2022)
The acoustic quality of a theatrical or musical room is an important factor in a musical or theater performance because it affects how sound is conveyed from the stage to the audience. In this study, the acoustic quality of a room was evaluated using standard values or recommendation criteria for acoustic parameters for a room Salihara Black Box Theter Room. The response impulse is measured using a balloon popping sound source. The measurement results of the research object show that the space still does not meet the recommendation criteria for reverberation time (T30), early decay time (EDT), clarity (C80), and definition (D50).